A Single-Nucleotide Polymorphism in Serine-Threonine Kinase 11, the Gene Encoding Liver Kinase B1, Is a Risk Factor for Multiple Sclerosis. (17th February 2015) - Boullerne, Anne I.; Skias, Demetrios; Hartman, Elizabeth M.; Testai, Fernando D.; Kalinin, Sergey; Polak, Paul E.; Feinstein, Douglas L.
We identified a family in which five siblings were diagnosed with multiple sclerosis (MS) or clinically isolated syndrome. Several women in the maternal lineage have comorbidities typically associated with Peutz Jeghers Syndrome, a rare autosomal-dominant disease caused by mutations in the serine-threonine-kinase 11 (STK11) gene, which encodes liver kinase B1. Sequence analysis of DNA from one sibling identified a single-nucleotide polymorphism (SNP) within STK11 intron 5. This SNP (dbSNP ID: rs9282860) was identified by TaqMan polymerase chain reaction (PCR) assays in DNA samples available from two other siblings. Further screening was carried out in samples from 654 relapsing-remitting MS patients, 100 primary progressive MS patients, and 661 controls. The STK11-SNP has increased frequency in all female patients versus controls (odds ratio = 1.66, 95% CI = 1.05, 2.64, p  = .032). The STK11-SNP was not associated with disease duration or onset; however, it was significantly associated with reduced severity (assessed by MS severity scores), with the lowest scores in patients who also harbored the HLA-DRB1*1501 allele. In vitro studies showed that peripheral blood mononuclear cells from members of the family were more sensitive to the mitochondrial inhibitor metformin than cells from MS patients with the major STK11 allele. The increased association of SNP rs9282860 in women with MS defines this variant as a genetic risk factor. The lower disease severity observed in the context of HLA-DRB1*1501 combined with limited in vitro studies raises the provocative possibility that cells harboring the STK11-SNP could be targeted by drugs which increase metabolic stress.